2011
DOI: 10.1093/toxsci/kfr194
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Ethylene and Ethylene Oxide in Subcellular Fractions of Lungs and Livers of Male B6C3F1 Mice and Male Fischer 344 Rats and of Human Livers

Abstract: Ethylene (ET) is metabolized in mammals to the carcinogenic ethylene oxide (EO). Although both gases are of high industrial relevance, only limited data exist on the toxicokinetics of ET in mice and of EO in humans. Metabolism of ET is related to cytochrome P450-dependent mono-oxygenase (CYP) and of EO to epoxide hydrolase (EH) and glutathione S-transferase (GST). Kinetics of ET metabolism to EO and of elimination of EO were investigated in headspace vessels containing incubations of subcellular fractions of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…In the rat lung microsomes the EPHX1 activity was, in turn, higher than in the lung microsomes of the mouse, the species most susceptible to the lung carcinogenic action of butadiene (see Table 5). Li et al (2011a) observed in human pulmonary microsomes mEH activity toward ethylene oxide as substrate (but not in pulmonary microsomes of rats or mice). Nishimura and Naito (2006) observed in the human lung modest levels of EPHX2 mRNA.…”
Section: Microsomal Epoxide Hydrolase (Ephx1 or Meh Or Eh1) Transcriptsmentioning
confidence: 74%
See 2 more Smart Citations
“…In the rat lung microsomes the EPHX1 activity was, in turn, higher than in the lung microsomes of the mouse, the species most susceptible to the lung carcinogenic action of butadiene (see Table 5). Li et al (2011a) observed in human pulmonary microsomes mEH activity toward ethylene oxide as substrate (but not in pulmonary microsomes of rats or mice). Nishimura and Naito (2006) observed in the human lung modest levels of EPHX2 mRNA.…”
Section: Microsomal Epoxide Hydrolase (Ephx1 or Meh Or Eh1) Transcriptsmentioning
confidence: 74%
“…Abdull Razis et al (2011) observed increases in GST activity toward CDNB as substrate also upon exposure of the precision-cut rat lung slices to the isothiocyanate precursor glucosinolate, glucoraphanin. Li et al (2011a) observed in rat pulmonary cytosol GST activity toward ethylene oxide as substrate. Zheng et al (2014) observed that GST activity toward the prototypic substrate 4-hydroxynonenal was very high in rat lung 9000 g supernatant, higher than in the liver.…”
Section: Gst Transcriptsmentioning
confidence: 87%
See 1 more Smart Citation
“…Only one study shows human kinetics data on methyl bromide levels in blood, with the elimination kinetics for up to 21 days after a fatal accident [ 15 ]. Little human literature data indicate that both, methyl bromide and ethylene oxide, have longer half lives in humans than in experimental animals with 12–99 h for ethylene oxide and up to 11 days for methyl bromide (depending on concentration, exposure circumstances and genetic predispositions) [ 15 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…At high ET concentrations, the initial ET metabolism to EO is rather fast. Li et al (2011a) calculated on the basis of measurements in liver microsomes maximum rates ( V max ) of the ET metabolism (µmol/h/kg body weight) of 42.9 in mice and 28.9 in rats. The same authors explained why earlier published, much smaller V max values are incorrect.…”
Section: Discussionmentioning
confidence: 99%